Professional node.js : building javascript based scalable software - Teixeira, Pedro Dennis, ....- (Indianapolis (Ind.) : Wiley Pub., Inc., 2012)
Learn to build fast and scalable software in JavaScript with Node.js Node.js is a powerful and popular new framework for writing scalable network programs using JavaScript. This no nonsense book begins with an overview of Node.js and then quickly dives into the code, core concepts, and APIs. In-depth coverage pares down the essentials to cover debugging, unit testing, and flow control so that you can start building and testing your own modules right away.
Keywords: Node.js.